Implementasi Media Pembelajaran Inovatif di SD Kusuma Putra Surabaya - Cahyono Putra, Andhika; Pudji Estiasih, Soffia (Fakultas Ekonomi Universitas Islam Majapahit, 2023)
Education is a very important learning process in human life. one of them with the use of appropriate learning media can influence the teaching and learning process to be more effective and fun. Kusuma Putra Surabaya Elementary School is a school located in Pogot Jaya, Kenjeran, Surabaya, East Java. At these schools have problems to improve effective teaching in order to improve the quality of teaching and learning in schools. The implementation method in community service activities this time has 3 stages, the first is the introduction method, the second is the method of carrying out innovative learning media with the game method, and the third is the assessment method. After the learning media were carried out for 2 months, the students who took part in the innovative learning media activities were very enthusiastic about the activities and had a positive impact on education, which is a very important learning process in human life. one of them with the use of appropriate learning media can influence the teaching and learning process to be more effective and fun. Kusuma Putra Surabaya Elementary School is a school located in Pogot Jaya, Kenjeran, Surabaya, East Java. At these schools have problems to improve effective teaching in order to improve the quality of teaching and learning in schools. The implementation method in community service activities this time has 3 stages, the first is the introduction method, the second is the method of carrying out innovative learning media with the game method, and the third is the assessment method. After the learning media were carried out for 2 months, the students who took part in the innovative learning media activities were very enthusiastic about the activities and had a positive impact on increasing grades.